Synthesis and characterization of tungsten carbide and application to electrocatalytic hydrogen evolution. Issue 80 (11th August 2016) - Liu, Can; Zhou, Dali; Zhou, Jiabei; Xie, Zhen; Xia, Yi
Abstract : Tungsten carbide was synthesized and further hydrogen treated to remove excess carbon. Abstract : Tungsten carbide was synthesized and further hydrogen treated to remove excess carbon. The obtained WC with different carbon contents was investigated by XRD, TG, SEM, EDS, BET and Raman. This work evaluated the effect of excess carbon on the properties of WC as a support for platinum. The hydrogen evolution reaction (HER) activity was used as a metric to test the effect of excess carbon on the electrochemical activity in 0.5 M sulfuric acid using a linear sweep voltammogram (LSV). Pt deposited on WC after hydrogen treatment exhibited a better electrocatalytic performance than Pt deposited on untreated WC. The investigations show that the presence of excess carbon is harmful to HER activity.